PHONOLOGICAL ANALYSIS ON BLENDING AND SEGMENTING FOR EARLY LITERACY OF K-1 AND K-2 CHILDREN IN I CAN READ ENGLISH COURSE IN BANDUNG CITY - Bagus Herlambang; Ida Zuraida Supri (Universitas Widyatama, 2020)
The research deals with blending and segmenting of reading acquisition skills given to the Early Literacy of K-1 and K-2 Children in I Can Read English Course in Bandung City. The research aims at identifying (1) which skill should be taught first to the students of bilingual school (K1 and K2), blending or segmenting and (2) in using the blending and segmenting, which word divisions (CVC, VCC, CCV) should be taught first to the students of bilingual school (K1-K2). The main data source in this descriptive quantitative research is taken mainly from 38 students of I Can Read English Course studying in bilingual school of K1 and K2. The research stage consists of following steps: Dividing students into two groups, which will be taught Segmenting-Blending and Blending-Segmenting for ten (10) meetings, providing a list of three word division groups which will be used by the instructor later to test the student